Development of modified AES algorithm for data security - Kumar, Puneet; Rana, Shashi B. (Optik (Stuttgart), 2016)
Cryptography is a process by which information or messages can be sent from one user to another user which provides several security services such as confidentiality, data integrity or authentication to the wireless communication system. As there is need for secure communication, efficient cryptographic processing is required for good system performance. One of the basic fundamental tools used in information security is known as the signature. Thus, the security for internet banking, account passwords, emails accounts password etc. requires text protection in digital media. This paper presents the security and compression for the data with the advance encryption standard (AES). In our research, we increase the number of rounds (Nr) to 16 for the encryption and decryption process of AES algorithm, which results in more security to the system. Experimental results and Theoretical analysis proved that this AES technique provide high speed as well as less transfer of data over the unsecured channels.